Hubungan Pekerjaan dan Usia Dengan Angka Kejadian Hernia Inguinalis di RSUD Waled Cirebon Periode Januari 2022-Desember 2023 - Vivi Silviana Ramadani; Evan Wahyudy Ladala; Siti Maria Ulfah (EduInovasi: Journal of Basic Educational Studies, 2025)
Inguinal Hernia is the emergence of protrusion in the groin. The incidence of Inguinal Hernia in Indonesia is 75% compared to other hernias. Inguinal Hernia in West Java 4,567 cases. Inguinal Hernia occurs due to several factors, namely modifiable (obesity), and non-modifiable (age), and other factors such as work. to determine the correlation between occupation and age with the incidence of inguinal hernia at Waled Cirebon Regional Hospital. analytical observational study with a cross-sectional approach. Data collection was carried out secondary by collecting medical record data. The sampling method used the Lemeshow method many as 96 samples. Data analysis will be tested using a data processing application. The highest frequency of inguinal hernia patients at RSUD Waled Cirebon is 91.7% of patients with lateral inguinal hernia. The highest frequency of work was 83.3% of patients with physical work, and the highest age frequency was 71.9% in adults. The results of the contingency coefficient show that there is no correlation between occupation and the incidence of inguinal hernias (p=0.741), and there is no correlation between ages and the incidence of inguinal hernias (p= 0.927). there is no significant correlation between work and age with the incidence of inguinal hernia.